Defending the city's cleanliness with their lives? A study of road traffic collisions involving sanitation workers in China over five years - Lifeng Wei; Zhuowa Sha; Haonan Jia; Yidong Wang; Gangyu Zhang; Yuanheng Li; Yameng Wang; Shuang Zhou; Ying Wang; Chao Liu; Mingli Jiao; Jingfu Mao; et al. (BMC, 2021)
Abstract Background With increasing urbanization in developing countries, sanitation workers are frequently involved in road traffic collisions. Our purpose was to study specific collisions involving sanitation workers and provide decision-making suggestions and reference measures for the sanitation industry and urban managers to reduce the occurrence of collisions. Methods We obtained online news data about sanitation worker road traffic collisions in China between 2013 and 2017 and analyzed occurrence time and location, victim characteristics, and causes of collisions. Results In China, between 2013 and 2017, 511 road traffic collisions were reported, with the fewest in February and July. Most occurred around 5:00 a.m. in Eastern regions and in urban areas. Victims were mainly over 50 years old, with more females than males. Collisions usually resulted in death at the scene. The ambiguity of laws, the exploitation of workers through industry outsourcing, and the difficulty of processing claims may be the main factors preventing victims from obtaining legal compensation. Conclusions The most common cause of collisions was drivers' speeding, but workers also regularly risk death by crossing the road in pursuit of their duties. The absence of legal controls for environmental protection, the excessive pursuit of efficiency in urban governance, and the lack of basic education of sanitation workers are underlying causes of collisions. Raising awareness about sanitation worker road traffic collisions will help protect the work safety rights of this vulnerable group.